Relationship between the learning styles preferences and academic achievement - Awang, Halizah; Abd Samad, Noorazman; Mohd Faiz, Nur Sofurah; Roddin, Rohayu; Jamilu, Kankia (IOP Publishing, 2017)
The individual learning differences that have been much explored relate to differences in personality, learning styles, strategies and conceptual of learning. This article studies the learning style profile exhibited by students towards the academic achievement in Malaysian Polytechnic. The relationship between learning styles of Polytechnic students and their academic achievement based on VARK learning styles model. The target population was international business students of Malaysian Polytechnic. By means of randomly sampling method, 103 students were selected as sample of research. By descriptive - survey research method and a questionnaire adapted from VARK Learning Style Index, required data were collected. According to the results, no significantly difference between learning style and academic achievement of students. Students academic achievement was quite similar to their individual learning styles. These facts reveal that each learning style has its own strengths and weaknesses.